Dose-response of tomato fruit yield to far-red fraction in supplementary lighting - Vincenzi, Elena; Moehn, Aron; Katsadas, Emmanouil; Karbor, Sana; de Beer, Esther; Millenaar, Frank; Marcelis, Leo F M; Heuvelink, Ep (Frontiers in Plant Science, 2025)
Supplementary LED lighting in greenhouse horticulture is typically rich in red light (R; 600–700 nm), while it lacks far-red light (FR; 700–800 nm), resulting in growing conditions with lower-than-solar far-red fractions [<0.46; FR/(R + FR)]. In these light environments, the addition of FR can improve tomato harvest index and fruit yield (ripe fruit fresh weight). While fruit yield increases linearly with the dose of FR at low FR fractions (0.1–0.28), it is unknown whether this relationship holds at higher FR levels, up to and above solar FR fractions. In this study, the relationship between tomato fruit yield and the FR fraction in supplementary lighting was quantified. Two cluster tomato cultivars ‘Foundation’ and ‘Trevine’ were grown in two greenhouse compartments for 20 weeks during the winter season (September to February). Different fractions of supplementary FR (0.22 to 0.49) were applied while maintaining a constant supplementary photosynthetic photon flux density of 250 µmol m−2 s−1 and 16-hour photoperiod. A yield component analysis was used to identify the key physiological drivers of the FR effect on yield. Additionally, fruit quality at harvest (total soluble solids, soluble sugars, and pH) and shelf-life were assessed. Additional FR increased fruit yield up to an FR fraction of 0.40, where the highest effect was recorded (+16% fruit yield for both cultivars). Fruit yield increases under additional FR were mostly associated with increased plant dry weight, with a small yet significant increase in the fraction of dry matter partitioned to the fruits. The radiation use efficiency (g fruit fresh weight mol−1) and electricity use efficiency of supplementary lighting (g fruit fresh weight kWh−1) decreased at higher FR fractions (0.44 and 0.49). Finally, additional FR had a minimal effect on fruit quality and shelf-life. We conclude that adding FR to supplementary lighting can increase tomato fruit yield linearly up to an FR fraction of 0.40, while at higher FR fractions, further increases in FR have limited or even negative effects on yield and decrease radiation and electricity use efficiency.